Degenerative Cervical Spondylosis: A Cause of Vertigo?. Issue 5 (June 2023) - Shende, Chetan; Rathod, Tushar; Marathe, Nandan; Mohanty, Shubhranshu; Kamble, Prashant; Mallepally, Abhinandan Reddy; Sathe, Ashwin
Study Design: Prospective observational study. Objectives: Studying the effect of degenerative cervical spondylosis(CS) on blood flow velocity of vertebral artery (VA) during cervical spine rotation in different head positions and its association with vertigo. Introduction: Vertigo is one of the most common complaints seen in an out-patient clinic. Its association with CS remains an enigma for a treating physician. This study planned to systematically analyze the association between vertigo and CS by evaluating VA blood flow dynamics in different head positions. Methods: 100 patients with ages ranging from 20-80 years were recruited. First group of 50 patients with CS with vertigo were compared with second study group of 50 patients having CS without vertigo. Cervical radiographs were used to evaluate CS using cervical degenerative index (CDI). Color doppler was used to measure VA blood flow with head in neutral position and 60° lateral rotation with 30° extension. Same procedure was repeated on opposite side. Measurements performed included peak systolic blood flow velocity(PSV) and end diastolic blood flow velocity (EDV). Results: Among patients with CS, patients having vertigo showed significantly more evident degenerative changes (CDI ≥25) ( P =<0.001). High grade CS patients (CDI ≥25) with vertigo had statistically significant lower blood flow parameters with head rotation in the left and right VAs as compared to CS patients without vertigo. Conclusion: This study highlights important pathophysiological mechanism of vertigo observed in patients of CS. The magnitude of reduction in VA blood flow was significantly higher in patients with advanced CS presenting as vertigo.